EFL learners’ metaphors and images about foreign language learning - Farjami, Hadi (Studies in Second Language Learning and Teaching, 2012)
In this paper, I will argue that awareness of images and metaphors held by foreign language learners about the nature of the target language and its learning can be of substantial value and provide teaching practitioners with useful insights about how to deal with various language learning problems. To elicit images which learners hold about foreign language learning, a questionnaire was given to 350 learners of English in different places in Iran. The questionnaire asked the respondents to provide images about learning a foreign language by using a sentence completion task: “Learning a foreign language is like . . .” The responses gained in 200 questionnaires were content-analyzed and the identified images and metaphors were summarized under more broad-ranging categories. The information that the metaphors and the resulting metaphorical categories provide and the theoretical interpretations which can plausibly be made are discussed in some detail and put in a cognitive-psychological perspective.